Macrocyclic Hosts in Asymmetric Phase-Transfer Catalyzed Reactions - Schettini, Rosaria; Sicignano, Marina; De Riccardis, Francesco; Izzo, Irene; Della Sala, Giorgio (Synthesis, 2018)
The introduction and development of neutral macrocyclic hosts capable of complexing ions within their pre-organized cavity, has been of utmost importance in supramolecular chemistry. Their ability to form stable organic-soluble metal–macrocycle complexes opened up the way to their application in phase-transfer catalysis (PTC) as a viable alternative to quaternary onium salts. In particular, their conformationally rigid preorganized backbone, accommodating organic substrates in defined orientations, promotes highly efficient stereoselective reactions. This short review summarizes the applications of neutral macrocyclic hosts in stereoselective PTC, highlighting the difference and possible complementarity with quaternary ammonium salts.1 Introduction2 Crown Ethers and Related Coronands2.1 Enantioselective PTC with Chiral Macrocyclic Coronands2.2 Enantioselective PTC Reactions Catalyzed by Chiral Quaternary Ammonium Salts with Achiral Crown Ether Co-catalysts3 Cyclic Peptoids4 Miscellaneous Chiral Macrocyclic Hosts5 Summary and Outlook
Keywords: asymmetric catalysis; crown compounds; host-guest systems; macrocycles; phase-transfer catalysis; calixarenes; cyclic peptoids